Studying Strategies to Create Value for OKPHOPTOK Store - chanthip, viengnakhone (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This research aims to investigate the production process used to create product value at an outlet store and to examine customer perceptions of product value. A quantitative research method was employed, targeting 138 customers who use products from an outlet store located in Luang Prabang Capital and Luang Prabang Province. Data were collected through questionnaires and analyzed using frequency, percentage, mean, and standard deviation. The findings reveal that the production process involves the import of key production factors, including raw materials, capital, labor, and equipment. The transformation process consists of five main steps. The store’s output includes six product categories: bags, clothing, household appliances, jewelry, DIY products, and home décor. Each production stage is carefully designed to add value and enhance customer satisfaction. Over time, sales across all product types have increased, primarily due to strategic improvements such as online store development, website upgrades, and expanded online advertising. These efforts have significantly improved product accessibility and appeal. Regarding perceived product value, customers rated the store’s image highest, followed by service quality, staff performance, and product attractiveness. However, moderate satisfaction was expressed concerning product quality in terms of meeting customer needs, durability, and the availability of various colors and designs. In terms of service value, customers highly recognized four main dimensions: product, service, staff, and brand image. Among these, brand image referred to in this study as the "stealth aspect" received the highest average rating. Nevertheless, moderate ratings were again observed for specific product features such as suitability, longevity, and variety.